2021
DOI: 10.1111/jpn.13643
|View full text |Cite
|
Sign up to set email alerts
|

A Fibre‐ vs. cereal grain‐based diet: Which is better for horse welfare? Effects on intestinal permeability, muscle characteristics and oxidative status in horses reared for meat production

Abstract: Horses reared for meat production are fed high amounts of cereal grains in comparison with horses raised for other purposes. Such feeding practice may lead to risk of poor welfare consequences. The aim of this study was to investigate the effects of two feeding practices on selected metabolic parameters and production aspects. Nineteen Bardigiano horses, 14.3 ± 0.7 months of age, were randomly assigned to two groups—one fed with high amounts of cereal grains (HCG; n = 9; 43% hay plus 57% cereal grain‐based pel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 64 publications
(94 reference statements)
3
34
0
Order By: Relevance
“…In fact, in older donkeys it is possible to determine a higher amount of IMF compared to younger animals [ 36 ]. Results obtained in this study confirmed that animal diet can significantly affect IMF and its fatty acid profile [ 37 ]. In equid meat, it is possible to determine small amounts of residual glycogen, even if significant differences can be detected among different muscles [ 38 ].…”
Section: Discussionsupporting
confidence: 76%
“…In fact, in older donkeys it is possible to determine a higher amount of IMF compared to younger animals [ 36 ]. Results obtained in this study confirmed that animal diet can significantly affect IMF and its fatty acid profile [ 37 ]. In equid meat, it is possible to determine small amounts of residual glycogen, even if significant differences can be detected among different muscles [ 38 ].…”
Section: Discussionsupporting
confidence: 76%
“…The project compares the effects of a standard feeding regime, adopted by intensive farming systems rearing horses for meat purposes, based on a high starch diet (HS) with a novel feeding regime strategy based on a high fibre diet (HF). The project was organised to study the effects of the two diets on: welfare [ 6 ], behavioural activities [ 14 ], meat production [ 42 ] and gut health.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid the repetition of data that has already been published, a brief summary of the experimental trial is reported below; further details can be found in Raspa et al 2021 [ 42 ]. The trial was approved by the Ethical Committee of the Department of Veterinary Sciences of the University of Turin (Italy, Prot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…unsuitability [1] . Horses are adapted to a slow and almost continual intake of a diet rich in structural fiber and low in rapidly hydrolyzable carbohydrates [2] . Hay can supply the fiber requirements for the production of volatile fatty acids by fibrolytic bacteria in the hindgut [3] .…”
Section: Introductionmentioning
confidence: 99%